Group Mentoring and Professionalism: A Programme Evaluation - Ritchie, A.; Genoni, Paul (Emerald, 2002)
This evaluative research represents the first report in the literature to date in which a group mentoring programme has been evaluated using a quasi-experimental research design. Results indicated that the programme was effective in one domain of professionalism, the main outcome variable; and that career-development outcomes were significantly higher in programme participants. In addition to the previously established functions of mentoring (career and psychosocial development), the research suggests that the conceptual basis of mentoring should be expanded to include the function of professionalism. This has implications for both the practical aspects of mentoring programme development and for future evaluative research. Data were collected by means of pre- and post-test questionnaires and analysed by multiple regression analysis.